Pemberian Pupuk Guano Dengan Dosis Berbeda Terhadap Produksi Rumput Ruzi (Bachiaria Ruziziensis) - Nikmah, Askura; Ridhana, Fita; Rahmawati, Rahmawati; Perdana, Aprian (Fapertago, 2021)
Ruzi grass (Bachiaria ruziziensis) is a superior grass that is good for use as animal feed, this grass has not been widely cultivated in Central Aceh Regency. The method used in this study was a non-factorial randomized block design (RAK) with 4 treatments, namely 0 tons-1,10 tons-1,15 tons-1,20 tons-1 and 3 replications. The results showed that the application of guano fertilizer at a dose of 20 tons/ha had a significant effect on the production, height, wet weight, and number of shoots of Ruzi Grass and the application of guano fertilizer at a dose of 0 tons/ha had no significant effect on the height, wet weight, and number of shoots of Ruzi Grass. .